Pengaruh Knowledge Sharing, Self Confidence dan Employee Engagement terhadap Kepuasan Kerja Karyawan dengan Komunikasi Organisasi sebagai Variabel Intervening - Mila Febriani Dzun Nur Ain; Slamet Bambang Riono; Azizah Indriyani; Muhammad Syaifulloh; Nur Khojin (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the effects of knowledge sharing, self-confidence, and employee engagement on employee job satisfaction, with organizational communication as an intervening variable. The study employed a quantitative approach through an empirical survey-based design. Data were analyzed using Structural Equation Modeling Partial Least Square (SEM-PLS). The research population consisted of 74 active employees at Toserba Mayga Sitanggal, with a saturated sampling technique, and data were collected using Likert-scale questionnaires. The study is expected to provide a more comprehensive understanding of the factors influencing employee job satisfaction through organizational communication mechanisms. The results indicate that knowledge sharing has a positive but not significant effect on job satisfaction (T-statistic = 1.918, p-value = 0.055). Self-confidence does not have a significant effect on job satisfaction (T-statistic = 1.639, p-value = 0.101), and employee engagement also shows no significant effect on job satisfaction (T-statistic = 0.716, p-value = 0.474). In contrast, knowledge sharing has a positive and significant effect on organizational communication (T-statistic = 4.943, p-value = 0.000), and self-confidence also has a positive and significant effect on organizational communication (T-statistic = 2.074, p-value = 0.038). Employee engagement, however, does not significantly affect organizational communication (T-statistic = 0.730, p-value = 0.465). Organizational communication has a positive and significant effect on job satisfaction (T-statistic = 4.570, p-value = 0.000). Mediation analysis shows that organizational communication significantly mediates the relationship between knowledge sharing and job satisfaction (p-value = 0.001). However, there is no significant mediating effect of organizational communication on the relationship between self-confidence and job satisfaction (p-value = 0.069), nor between employee engagement and job satisfaction (p-value = 0.478).